2004
DOI: 10.1098/rspb.2003.2557
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for mycorrhizal races in a cheating orchid

Abstract: Disruptive selection on habitat or host-specificity has contributed to the diversification of several animal groups, especially plant-feeding insects. Photosynthetic plants typically associate with a broad range of mycorrhizal fungi, while non-photosynthetic plants that capture energy from mycorrhizal fungi ('mycoheterotrophs') are often specialized towards particular taxa. Sister myco-heterotroph species are often specialized towards different fungal taxa, suggesting rapid evolutionary shifts in specificity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
102
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(106 citation statements)
references
References 64 publications
2
102
2
Order By: Relevance
“…Conservation approaches for these species are closely dependent on determination of appropriate ex situ methods of growth so that more seed and /or seedlings can be used to stabilise natural populations. As these orchid species depend on ECM fungi for their nutrition (Taylor et al 2004;Selosse et al 2004; Dearnaley and Le Brocque 2006 but see Yagame et al 2007 for a recent review of MH orchids that can be cultivated with non ECM fungi) ex situ growth will require establishing tripartite symbiotic interactions with tree seedlings, ECM fungi and orchids under controlled conditions. Warcup (1985Warcup ( , 1988Warcup ( , 1991, McKendrick et al (2000) and Bougoure (pers.…”
Section: Determination Of Conservation Methods For Orchids Reliant Onmentioning
confidence: 99%
See 1 more Smart Citation
“…Conservation approaches for these species are closely dependent on determination of appropriate ex situ methods of growth so that more seed and /or seedlings can be used to stabilise natural populations. As these orchid species depend on ECM fungi for their nutrition (Taylor et al 2004;Selosse et al 2004; Dearnaley and Le Brocque 2006 but see Yagame et al 2007 for a recent review of MH orchids that can be cultivated with non ECM fungi) ex situ growth will require establishing tripartite symbiotic interactions with tree seedlings, ECM fungi and orchids under controlled conditions. Warcup (1985Warcup ( , 1988Warcup ( , 1991, McKendrick et al (2000) and Bougoure (pers.…”
Section: Determination Of Conservation Methods For Orchids Reliant Onmentioning
confidence: 99%
“…Helaxectris spp., Epipactis spp., Dipodium spp. (Taylor et al 2004;Selosse et al 2004;Dearnaley and Le Brocque 2006) and further study (eg. mycobiont identification; stable C and N isotope ratios, CO 2 exchanges) is required of rare chlorophyllous species to confirm physiological status (ie.…”
Section: Determination Of Conservation Methods For Orchids Reliant Onmentioning
confidence: 99%
“…Early molecular studies have revealed that terrestrial orchids interact with a wide range of mycorrhizal fungi. Some orchids are extreme specialists and are associated to a single fungal species (MCCORMICK et al 2004, TAYLOR et al 2004, DEARLANEY 2007, SHEFFERSON et al 2008, while others are generalists, hosting many different fungi (MCCORMICK et al 2006, BONNAR-DEAUX et al 2007, IRWIN et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Raf. where a particular genotype will only associate with specific subclades in the Russulaceae Taylor et al 2004). The few known exceptions to this pattern of specificity are albino mutants of normally green orchids in the genera Cephalanthera and Epipactis that were found to associate with the same suite of ectomycorrhizal (EM) fungi as green individuals (Selosse et al 2004;Julou et al 2005;Abadie et al 2006).…”
Section: Introductionmentioning
confidence: 99%